2022
DOI: 10.1073/pnas.2201922119
|View full text |Cite
|
Sign up to set email alerts
|

The presence and role of the intermediary CO reservoir in heterogeneous electroreduction of CO 2

Abstract: Significance The electroconversion of CO 2 to value-added products is a promising path to sustainable fuels and chemicals. However, the microenvironment that is created during CO 2 electroreduction near the surface of heterogeneous Cu electrocatalysts remains unknown. Its understanding can lead to the development of ways to improve activity and selectivity toward multicarbon products. This work introduces a method called on-stream substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…20,36,47,59 Recently, Roldan-Cuenya et al have shown that these vibrations can be used as a probe to measure the surface coverage of CO by taking the ratio of the two low-Raman shift vibrations (280 and 360 cm −1 ), 20 which is also possible through onstream substitution of the reactant isotope. 60 In the potential window of −0.55 to −0.85 V RHE , it is observed that the high-frequency-band (HFB) CO band at 2090 cm −1 dominates and has a lowfrequency-band (LFB) CO tail centered around 2050 cm −1 . These potential-and time-dependent CO stretching vibrations are attributed to the stochastic behavior of adsorbed CO and are extensively described in our previous work, where we studied the time-dependent behavior of adsorbed CO at fixed cathodic biases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,36,47,59 Recently, Roldan-Cuenya et al have shown that these vibrations can be used as a probe to measure the surface coverage of CO by taking the ratio of the two low-Raman shift vibrations (280 and 360 cm −1 ), 20 which is also possible through onstream substitution of the reactant isotope. 60 In the potential window of −0.55 to −0.85 V RHE , it is observed that the high-frequency-band (HFB) CO band at 2090 cm −1 dominates and has a lowfrequency-band (LFB) CO tail centered around 2050 cm −1 . These potential-and time-dependent CO stretching vibrations are attributed to the stochastic behavior of adsorbed CO and are extensively described in our previous work, where we studied the time-dependent behavior of adsorbed CO at fixed cathodic biases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Around −0.55 V RHE , vibrations at 2090, 360, and 280 cm –1 appear simultaneously. These vibrations are typically assigned to the linear CO stretching, Cu-C stretching, and Cu-CO bending of adsorbed (linear) CO on Cu, respectively. ,,, Recently, Roldan-Cuenya et al have shown that these vibrations can be used as a probe to measure the surface coverage of CO by taking the ratio of the two low-Raman shift vibrations (280 and 360 cm –1 ), which is also possible through onstream substitution of the reactant isotope . In the potential window of −0.55 to −0.85 V RHE , it is observed that the high-frequency-band (HFB) CO band at 2090 cm –1 dominates and has a low-frequency-band (LFB) CO tail centered around 2050 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…25 This was attributed to having to build up a necessary concentration of intermediates (carbon monoxide) in its microenvironment for carbon-carbon coupling. 26 Systems using planar silicon for wet-side illumination CO2R (incident light, catalyst, and electrolyte on same side) show low current densities and selectivity toward multi-carbons due to low mass loading 27,28 while a microwire array with large mass loading (>300 µg/cm 2 ) showed limited stability (≤1 hour) likely due to catalyst deactivation. 29 Considering that practical applications require long term operations with high current densities (mA scale), 30 it remains a major challenge to discover more durable and selective PEC CO2R systems.…”
mentioning
confidence: 99%
“…High selectivity toward multicarbon products can be achieved by controlling the current density at a given potential by modulating the surface area of copper, the only known metal capable of carbon–carbon coupling, and by using nanostructures with undercoordinated sites . This was attributed to having to build up a necessary concentration of intermediates (carbon monoxide) in its microenvironment for carbon–carbon coupling . Systems using planar silicon for wet-side illumination CO 2 R (incident light, catalyst, and electrolyte on the same side) show low current densities and selectivity toward multicarbons due to low mass loading, , while a microwire array with large mass loading (>300 μg/cm 2 ) showed limited stability (≤1 h) likely due to catalyst deactivation .…”
mentioning
confidence: 99%
“…The residence time of the reactor determined the further conversion ratio of CO produced from CO 2 reduction. Furthermore, Louisia et al revealed the presence of a reservoir of unadsorbed CO intermediate near the catalyst surface through an on-stream isotope substitution experiment (Figure b) . If such a reservoir does not exist in the proximity of the Cu surface and all C 2+ products are derived from adsorbed *CO intermediates, a monolayer of *CO does not provide adequate CO intermediates to facilitate the formation of C 2+ products.…”
Section: Effects Of Co-formation Catalysts On Cu Catalystsmentioning
confidence: 99%